Method for preparing configured nickel-based abrasion-resistant composite coating through high-speed laser cladding

By combining pulsed laser and continuous laser cladding technology with the in-situ reaction of MoAlB compound powder, a crack-free and bubble-free structured nickel-based coating was prepared, which solved the problems of uneven coating structure and high thermal stress during the laser cladding process and improved the comprehensive performance and application adaptability of the coating.

CN120666329APending Publication Date: 2025-09-19CHINA YANGTZE POWER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511043809.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-28
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing laser cladding technology is prone to cracks and bubbles when preparing nickel-based coatings, and the coating structure is uneven, affecting the overall performance. In particular, the thermal stress is large during high-speed laser cladding, resulting in a decrease in coating quality and performance.

Method used

By combining pulsed laser-assisted beam shaping technology with continuous laser cladding, and regulating the interaction between laser beams of different forms and composite powders, a crack-free and bubble-free structured nickel-based coating is prepared. The enhanced structure optimizes the coating organization, inhibits the formation of thermal cracks, and forms a micro-nano synergistic reinforcement structure through the in-situ reaction of MoAlB compound powder and nickel-based alloy powder.

Benefits of technology

The nickel-based coating is crack-free, bubble-free, and has a dense structure with uniform structure, which improves the comprehensive performance of the coating. It has high hardness, high thermal stability and low coercivity, and is suitable for erosion resistance, high temperature resistance and paramagnetic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120666329A_ABST
    Figure CN120666329A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a configured nickel-based wear-resistant composite coating through high-speed laser cladding, which comprises the following steps: mixing nickel-based composite coating powder for 12 hours through a roller mixer at the speed of 30 rpm, and then putting the nickel-based composite coating powder into an electric heating constant-temperature vacuum drying oven at the temperature of 100-120 DEG C to dry the powder for 40-120 minutes; adding the dried powder into a powder cylinder; the parameters of high-speed laser cladding are set as follows: the laser power is 600-1100 W, the scanning speed is 3000-4000 mm / min, the powder feeding amount is 0.4-1.0 r / min, and the lap joint rate is 50-70%; high-speed laser cladding is carried out by adopting a coaxial powder feeding mode, and a high-quality crack-free coating is prepared by combining a pulse type laser cladding technology and a beam shaping technology. According to the method, the nickel-based composite coating without cracks and bubbles is prepared through a shaped flat-top light or rectangular light high-speed laser cladding method, a unique microstructure is formed through in-situ reaction in a laser cladding instantaneous high-temperature thermal field, the hardness, plasticity and other performance of a cladding layer are improved, the coercive force and magnetism of the material are regulated and controlled, and the nickel-based composite coating with the cracks and the bubbles is prepared. And a mechanical and magnetic fused high-performance cladding layer is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material surface modification, and particularly relates to a method for preparing a structured nickel-based wear-resistant composite coating by high-speed laser cladding. Background Art

[0002] In the engineering field, a considerable number of parts are damaged from the surface. For example, in corrosive media, solid particle wear, and erosion by solid-liquid two-phase mixed fluids, parts are usually damaged from the surface and gradually spread to the inside, eventually leading to overall wear, corrosion, and fracture of the parts, causing serious production accidents. Therefore, the surface of the parts needs to have comprehensive properties such as high surface wear resistance and erosion resistance. Taking the large-scale water conservancy projects in the Yangtze River Basin of my country as an example, the turbine blades are subjected to long-term erosion by river water containing sand and various trace ionic liquids, which causes severe erosion and wear on conventional metal materials represented by stainless steel, seriously affecting the operating efficiency of the hydropower station.

[0003] Laser cladding is a new technology that creates a heterogeneous hardened layer on metal surfaces, thereby achieving surface modification. However, the high laser energy, rapid heating rate, and high thermal stress often lead to defects such as cracks and bubbles in the cladding layer, seriously affecting its quality and performance. Therefore, it is necessary to adjust and modify the laser spot shape, control the heating rate and thermal stress, and suppress crack formation.

[0004] Nickel-based alloy powder is a commonly used powder system for laser cladding. It has excellent toughness, wettability, and corrosion resistance. However, nickel-based alloy powder is highly crack-sensitive and the coating hardness is relatively low. High-speed laser cladding, a process characterized by large temperature gradients and rapid cooling rates, can easily lead to defects such as cracks and bubbles. Preheating the substrate is generally used to reduce surface cracks in the coating, but preheating not only causes oxidation on the substrate surface but also affects the interfacial bonding between the coating and the substrate.

[0005] Due to the characteristics of high-speed laser cladding technology, such as large temperature gradients in the molten pool, rapid cooling rates, and transient non-equilibrium solidification, the resulting cladding layer has an uneven microstructure. At the bottom of the molten pool, the degree of undercooling is small, and the cladding layer is mostly planar crystals. In the middle of the molten pool, the cladding layer is mostly coarse columnar crystals growing along the direction of the heat flow. At the top of the molten pool, the degree of undercooling is large, and the cladding layer is mostly fine crystals. The uneven microstructure has a significant impact on the overall performance of the cladding layer. Therefore, it is proposed to add MoAlB compound powder with an in-situ reaction strengthening effect and assist in laser pulse control of the cladding layer microstructure. On the one hand, the thermal cracking tendency caused by continuous high-speed, high-power laser planar cladding can be limitedly alleviated. On the other hand, the unique MoAlB ceramic and nickel-based alloy components produce an in-situ autogenous reaction to form micro-nano synergistic reinforcement, which gives the cladding layer a serrated macro-hardened layer while giving the reinforcement therein a "core-shell" microscopic feature, thereby significantly improving its overall performance. Summary of the Invention

[0006] The present invention provides a method for preparing a structured nickel-based wear-resistant composite coating by high-speed laser cladding. A crack-free and bubble-free composite nickel-based coating is prepared by adopting pulsed laser-assisted beam shaping technology. The pulsed laser is combined with a continuous laser cladding method and the reinforcement structure is optimized to improve the coating tissue characteristics and enhance the comprehensive mechanical properties of the coating. A dense and complete nickel-based composite coating without cracks or bubbles is obtained, making the coating tissue more uniform and presenting macro- and micro-structured characteristics, thereby improving its comprehensive performance.

[0007] The technical solution adopted in the present invention is: A method for preparing a structured nickel-based wear-resistant composite coating by high-speed laser cladding, the method comprising the following steps: S1: mixing the nickel-based composite coating powder with a roller mixer and then baking the powder; S2 adds the dried powder into the powder barrel; The S3 utilizes coaxial powder feeding for high-speed laser cladding, combining pulsed laser cladding technology with continuous laser beam shaping to produce high-quality, crack-free, high-performance coatings. During the first layer of high-speed laser cladding, a pulsed laser is applied. The fed composite powder rapidly melts within the micromolten pool generated by the pulsed laser, creating a zigzag-shaped, staggered composite layer on the substrate's subsurface, reducing internal stress and cracking in the cladding layer. During the second, third, and fourth layers of high-speed laser cladding, continuous high-speed laser cladding is applied to form a high-hardness flat layer. This process is repeated, with three flat layers being clad after each zigzag layer. The cross-section of the zigzag layer forms an 80-90° angle between the hard layer and the horizontal. The cross-section of the zigzag layer measures 3-5 mm x 3-5 mm, with a spacing of 5 mm. By manipulating the interaction between the laser beam and the composite powder, the thermal field temperature distribution and thermal stress of the cladding layer are regulated, suppressing the formation of thermal cracks in the part. High-speed laser cladding is used to prepare micro-structured nickel-based wear-resistant coatings with comprehensive properties such as high hardness, high thermal stability and low coercive force, meeting the characteristics of erosion resistance, high temperature resistance and paramagnetism.

[0008] Preferably, the nickel-based composite coating powder in step S1 of step 2 comprises the following components by mass fraction: 17-27 wt% Cr, 6-8 wt% Fe, 4-5 wt% Si, 5-8 wt% B, 0.3-0.7 wt% C, less than 0.02 wt% O, and the balance being Ni, and the powder particle size is 40-100 μm. The Cr, Fe, C, and B elements added to the reinforcing powder react rapidly in situ with the reinforcement powder under high-speed laser cladding to form a special hard phase at the nanometer scale and a specific micrometer-scale microstructure.

[0009] Preferably, in step S1, reinforcement powder is further added to the nickel-based composite coating powder, and the reinforcement powder is MoAlB compound powder. Preferably, in step S1, the mixing time is 11-14 hours, the mixing speed is 20-40 rpm, and then the mixture is placed in an electric constant temperature vacuum drying oven at 100-120° C. and dried for 40-120 minutes.

[0010] Preferably, the scanning speed of step S3 is faster than that of traditional laser cladding technology, and the scanning speed adopted is 3000-4000 mm / min, the dilution rate of the cladding layer is low, the powder feeding rate is 0.4-1.0 r / min, and the overlap rate is 50-70%, thereby improving the cladding efficiency.

[0011] Preferably, the pulse frequency of the pulsed laser cladding technology in step S3 is 100-1000 Hz, the pulse width is 50-600 μs, and the power is 400-600 W; the continuous laser beam power is 600-1100 W, so that the cladding layer has a specific temperature gradient transient non-equilibrium solidification characteristic.

[0012] Preferably, the beam shaping technology in step S3 refers to the laser shape being a shaped circular flat top light or rectangular Gaussian light, the spot diameter of the circular flat top light is 3-7 mm, and the spot size of the rectangular Gaussian light is 4 mm×4 mm.

[0013] Further preferably, the amount of reinforcement powder added accounts for 25-35 wt% of the total amount of nickel-based composite coating powder, preferably 30 wt%. Further preferably, the purity of the MoAlB compound powder is above 95%, the particle size is 20-40 μm, and the equivalent particle size deviation rate is within 10%. Beneficial effects of the present invention: The present invention adopts the method of high-speed laser cladding with shaped flat top light or Gaussian rectangular light to prepare a nickel-based coating without cracks and bubbles, heats the workpiece evenly, does not need to preheat the substrate, prevents the generation of oxide scale on the substrate surface, improves the interface bonding between the coating and the substrate, has a smaller heat-affected zone, has a uniform and dense structure, and has a low dilution rate. The powder utilization rate can reach more than 90%, saving material costs; high-speed laser cladding adopts an increased laser scanning speed and an auxiliary pulse laser beam method to reduce the dilution rate of the coating, improve the powder utilization rate and reduce material loss; the nickel-based alloy powder is reinforced to make the coating structure present a configuration feature, improve the comprehensive mechanical properties of the coating, reduce residual stress, maintain high hardness, high wear resistance and high corrosion resistance. Through the composite of the Ni-based coating and the martensitic stainless steel substrate, the magnetism of the martensitic stainless steel can also be effectively reduced, reducing coercive force and hysteresis loss.

[0014] Specifically, nickel-based alloy powder is a highly crack-sensitive material, making it prone to cracks and bubbles during high-speed laser cladding, a process characterized by rapid heating and cooling. High-speed laser cladding technology, assisted by a flat-top beam or Gaussian rectangular beam pulsed laser, reduces the generation of bubbles and cracks, producing a dense coating with good interfacial bonding. The scanning speed is faster than that of traditional laser cladding technology, with a scanning speed of 3000mm / min-4000mm / min, and the dilution rate of the cladding layer is low; it has the characteristics of pulsed laser with a frequency of 100-1000Hz, which makes the cladding layer have specific temperature gradient transient non-equilibrium solidification characteristics.

[0015] The laser beam morphology is shaped into a circular flat top beam and a Gaussian rectangular beam. By regulating the interaction between the laser beam quality and the powder in different morphologies, the formation of thermal cracks in the parts is suppressed.

[0016] The powder matrix and reinforcement powder must be used in combination. When using MoAlB compound powder, it undergoes a rapid in-situ chemical reaction with the Cr, Fe, C, and B elements in the nickel-based composite coating powder under high-speed laser cladding to form a special nanoscale hard phase and a specific micron-scale microstructure. The Al element in MoAlB is the first to overflow from the layered crystal structure under the action of laser energy and reacts in-situ with the B and O elements in the mixed powder to form AlB2 and Al2O3. The remaining Mo element reacts with the C element in the mixed powder to form Mo2C. The B element in the hard phase and the B element in the mixed powder can react with the Fe element to form an Fe2B hard phase. Due to the transient solidification characteristics of high-speed laser cladding, MoAlB mainly reacts in situ at the periphery of the powder, so the reinforcement in the coating organization presents a "core-shell" configuration structure, including the MoAlB compound body and the MoB phase after the overflow of Al element as the "core", and the in-situ self-generated Mo2C+Fe2B+AlB2 and other reinforcement phases forming the "shell". Since Mo2C, Fe2B, and AlB2 compounds have excellent metallic properties, toughness, and polar covalent bond characteristics, they can give the composite coating a good gradient transition feature from the reinforcement phase to the matrix alloy, thereby giving the composite coating outstanding wear resistance, corrosion resistance and machinability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the macromorphology of the crack-free nickel-based coating prepared by high-speed laser cladding.

[0018] Figure 2 It is a core-shell structure at the edge of the reinforcement particles of the nickel-based alloy coating structure.

[0019] Figure 3 It is the microstructure morphology in nickel-based composite coating.

[0020] Figure 4 It is the indentation of the toughness test of nickel-based coating.

[0021] Figure 5 It is a magnetic comparison between the original stainless steel sample and the stainless steel sample with nickel-based coating.

[0022] Figure 6 It is the micro-Vickers hardness of the nickel-based coating before and after heat treatment at 600℃ and 800℃. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be further described below with reference to the embodiments, but the scope of protection of the present invention is not limited thereto. The specific embodiments described herein are only for the purpose of illustrating and explaining the present disclosure and are not intended to limit the present disclosure. Equivalent substitutions or corresponding improvements made to the contents of the present invention are still within the scope of protection of the present invention.

[0024] S1. The nickel-based composite coating powder was mixed by a stick mixer for 12h at a speed of 30rpm and then placed in an electric constant temperature vacuum drying oven at 100-120 ℃ for 40-120min; S2. Add the dried powder to the powder cartridge; S3. High-speed laser cladding is performed using a coaxial powder feeding method to prepare a (50-80) mm × (50-80) mm coating on the substrate. When high-speed laser cladding is performed for the first layer, a pulsed laser is applied. The composite powder fed is rapidly melted under the action of the micro-molten pool generated by the pulsed laser, corresponding to the formation of a serrated staggered composite layer in the sub-surface area of ​​the substrate, reducing the internal stress and cracking tendency of the cladding layer. When high-speed laser cladding is performed for the second to fourth layers, a continuous high-speed laser is applied to form a high-hardness flat layer. Similarly, after cladding one serrated layer, three flat layers are clad. The side of the hard layer of the cross-section of the serrated layer forms an angle of 80 to 90 degrees with the horizontal plane. The cross-section of the serrated layer has a size of 3-5 mm × 3-5 mm, with a spacing of 5 mm. By regulating the interaction process between the laser beam of different forms and the composite powder, the thermal field temperature distribution and thermal stress of the cladding layer are regulated, thereby suppressing the formation of thermal cracks in the part. S4. Perform surface flaw detection and cross-section observation on the substrate after cladding; S5. The surface-modified material is heated and held at 600°C, 700°C, and 800°C for 1 hour and then cooled to room temperature. S6. Test the hardness and structure of the coating after heating and holding at different temperatures, and examine the thermal stability of its structure and performance.

[0025] According to the above solution, preferably, before step S3, the substrate is polished to ensure that its roughness is below 3.2, and is cleaned with acetone and dried for later use.

[0026] The present invention will be described in detail below with reference to the embodiments. It should be noted that, unless there is a conflict, the embodiments and features in the embodiments of the present application can be combined with each other. Example 1 A method for preparing a structured nickel-based wear-resistant composite coating by high-speed laser cladding comprises the following steps: S1. Mix nickel-based alloy powder and MoAlB powder (particle size 20-40 μm), the addition amount accounting for 30 wt% of the nickel-based alloy powder, in a roller mixer for 12 hours at a speed of 30 rpm, and then place the powder in an electric constant temperature vacuum drying oven at 120°C for 40 minutes. The nickel-based composite coating powder comprises the following components by mass fraction: Cr 25 wt%, Fe 7 wt%, Si 4.5 wt%, B 7 wt%, C 0.5 wt%, O 0.005 wt%, with the balance being Ni, and the powder particle size is 40-100 μm. S2, adding the dried powder into the powder tube; S3: High-speed laser cladding was performed using coaxial powder feeding to prepare an 80mm×80mm coating on the substrate. During the first layer of high-speed laser cladding, a pulsed laser was applied at a frequency of 400Hz, a pulse width of 100μs, and a power of 400W. The fed composite powder was rapidly melted by the micro-molten pool generated by the pulsed laser, producing a jagged interlaced composite layer in the subsurface region of the substrate. The side of the hard layer in the cross section formed an 80° angle with the horizontal plane, and the cross-sectional dimensions were 3mm×3mm, with a spacing of 5mm. S4. During the second to fourth layers of high-speed laser cladding, continuous high-speed laser is applied to form a high-hardness flat layer. The laser morphology is a shaped circular flat top light with a spot diameter of 3mm. The continuous laser beam power is 600W, the scanning speed is 3000mm / min, the powder feeding rate is 0.4r / min, and the overlap rate is 70%. S5, repeat S3 and S4, cladding three flat layers after each cladding of one sawtooth layer, the sawtooth layer thickness is 200 μm, and the flat layer thickness is 400 μm; S6. Surface flaw detection and cross-section observation of the substrate after cladding are performed to prepare a coating with good bonding and no cracks. The macroscopic morphology of the coating surface is as shown in the attached figure. Figure 1 As shown, the laser cladding parameters of this embodiment can produce a nickel-based composite coating with no surface cracks or pore defects; S7. Take the original stainless steel material and the stainless steel composite material with the cladding layer for magnetic testing, and obtain the hysteresis loops of the two for comparison. The coating has a certain electromagnetic shielding effect on the stainless steel; S8. Prepare metallographic samples. After cladding, the reinforcement in the coating shows a "core-shell" configuration structure, including the "core" of ultra-high hardness MoAlB+MoB compound and the "shell" formed by the reinforcement phases such as Mo2C+Fe2B+AlB2. Figure 2 As shown in the figure, the high hardness composite hard phase is distributed around the in-situ self-generated hard phase to form a configurational feature. Figure 3 The microstructure of the nickel-based coating shows that by regulating the interaction between the laser beam and the composite powder, a dense microstructure and a good combination of the hard phase and the nickel matrix are achieved. Figure 4 ) It can be seen that the coating exhibits good toughness characteristics under the action of the hard indenter. Based on this, it is inferred that the cladding parameters of this embodiment can reduce the internal stress of the cladding layer, slow down the cracking tendency, and inhibit the formation of thermal cracks in the parts.

[0027] Example 2 A method for preparing a structured nickel-based wear-resistant composite coating by high-speed laser cladding comprises the following steps: S1. Nickel-based alloy powder and MoAlB powder (particle size 20-40 μm, added in an amount accounting for 30 wt% of the nickel-based alloy powder) were mixed in a roller mixer at 30 rpm for 12 hours and then dried in an electric constant-temperature vacuum drying oven at 100°C for 120 minutes. The nickel-based composite coating powder comprised the following components by mass fraction: Cr 25 wt%, Fe 7 wt%, Si 4.5 wt%, B 7 wt%, C 0.5 wt%, O 0.005 wt%, with the balance being Ni, and had a powder particle size of 40-100 μm. S2. Add the dried powder to the powder cartridge; S3. High-speed laser cladding was performed using coaxial powder feeding to produce an 80mm x 80mm coating on the substrate. During the first layer of high-speed laser cladding, a pulsed laser was applied at a frequency of 800Hz, a pulse width of 200μs, and a power of 600W. The fed composite powder rapidly melted in the micromolten pool generated by the pulsed laser, producing a jagged, staggered composite layer on the subsurface of the substrate. The hard layer side of the cross-section formed a 90° angle with the horizontal plane, and the cross-section measured 5mm x 5mm, with a spacing of 5mm. S4. During the second to fourth layers of high-speed laser cladding, a continuous high-speed laser was applied to form a high-hardness planar layer. The laser beam was a shaped rectangular Gaussian beam with a spot size of 4 mm × 4 mm. The continuous laser beam power was 1100 W, the scanning speed was 3500 mm / min, the powder feed rate was 0.8 r / min, and the overlap ratio was 60%. S5. Repeat S3 and S4, cladding three flat layers after each cladding of a sawtooth layer, with a sawtooth layer thickness of 225 μm and a flat layer thickness of 450 μm; S6. Perform surface flaw detection and cross-sectional observation on the substrate after cladding to produce a well-bonded, crack-free coating; S7. Take the stainless steel original material and the stainless steel composite material with cladding layer and perform magnetic testing to obtain the hysteresis loops of the two for comparison, as shown in the attached figure. Figure 5 As shown, the coating has a certain electromagnetic shielding effect on stainless steel; S8. Prepare metallographic samples. After cladding, the reinforcement in the coating shows a "core-shell" structure, including in-situ self-generated Mo2C+Fe2B+AlB2 reinforcement phase. The composite coating has outstanding hardness, wear resistance, corrosion resistance and paramagnetism. Figure 6 As shown in Figure 2, the hardness of the outer hard layer of the coating is twice that of the substrate, showing outstanding wear resistance. Example 3 A method for preparing a structured nickel-based wear-resistant composite coating by high-speed laser cladding comprises the following steps: S1. Nickel-based alloy powder and MoAlB powder (particle size 20-40 μm, added in an amount accounting for 30 wt% of the nickel-based alloy powder) were mixed in a roller mixer at 30 rpm for 12 hours and then dried in an electric constant-temperature vacuum drying oven at 110°C for 60 minutes. The nickel-based composite coating powder comprised the following components, by mass fraction: Cr 25 wt%, Fe 7 wt%, Si 4.5 wt%, B 7 wt%, C 0.5 wt%, O 0.005 wt%, with the balance being Ni, and had a powder particle size of 4-100 μm. S2. Add the dried powder to the powder cartridge; S3. High-speed laser cladding was performed using coaxial powder feeding to produce an 80mm x 80mm coating on the substrate. During the first layer of high-speed laser cladding, a pulsed laser was applied at a frequency of 600Hz, a pulse width of 400μs, and a power of 700W. The fed composite powder rapidly melted within the micromolten pool generated by the pulsed laser, producing a jagged, staggered composite layer on the subsurface of the substrate. The hard layer of the cross-section formed an 85° angle with the horizontal plane, with a cross-sectional dimension of 4mm x 4mm and a spacing of 4mm. S4. During the second to fourth layers of high-speed laser cladding, a continuous high-speed laser was applied to form a high-hardness flat layer. The laser morphology was a shaped circular flat top beam with a spot diameter of 4 mm. The continuous laser beam power was 1000 W, the scanning speed was 3000 mm / min, the powder feed rate was 0.8 r / min, and the overlap rate was 65%. S5. Repeat S3 and S4, cladding three flat layers after each cladding of a sawtooth layer, with a sawtooth layer thickness of 250 μm and a flat layer thickness of 425 μm; S6. Perform surface flaw detection and cross-sectional observation on the substrate after cladding to produce a well-bonded, crack-free coating; S7. Magnetic tests were performed on the original stainless steel material and the stainless steel composite material with the cladding layer. The hysteresis loops of the two were compared, indicating that the coating has a certain electromagnetic shielding effect on the stainless steel. S8. Metallographic specimens were prepared. After cladding, the reinforcement in the coating exhibited a core-shell structure, containing in-situ self-generated Mo2C+Fe2B+AlB2 reinforcement phases. This composite coating exhibited outstanding wear resistance, corrosion resistance, and machinability, effectively reducing the magnetism of martensitic stainless steel, and reducing coercive force and hysteresis loss.

[0028] Example 4 Based on Example 1, the diameter of the circular flat top light spot is 4 mm, and the rest is the same as Example 1.

[0029] Example 5 Based on Example 1, the diameter of the circular flat top light spot is 5 mm, and the rest is the same as Example 1.

[0030] Comparative Example 1 Based on Example 1, the diameter of the circular flat top light spot is 7 mm, and the rest is the same as Example 1.

[0031] Comparative Example 2 Based on Example 1, circular Gaussian light cladding is used for the 2nd to 4th layers, and the rest is the same as Example 1.

[0032] Comparative Example 3 Based on Example 1, a composite coating powder is used, comprising the following components by mass fraction: 17-27 wt% Cr, 6-8 wt% Ni, 4-5 wt% Si, 5-8 wt% B, 0.3-0.7 wt% C, less than 0.02 wt% O, and the balance being Fe. Other components are the same as in Example 1. Example 6 Based on Example 1, the pulse laser frequency is 100 Hz, the pulse width is 50 μs, the power is 600 W, and the rest is the same as Example 1.

[0033] Example 7 Based on Example 1, the pulse laser frequency is 800 Hz, the pulse width is 400 μs, the power is 700 W, and the rest is the same as Example 1.

[0034] Comparative Example 4 Based on Example 1, the pulse laser frequency is 1000 Hz, the pulse width is 600 μs, the power is 800 W, and the rest is the same as Example 1. Comparative Example 5 Based on Example 1, the difference is that step S3-S4, step S3 is continuous high-speed laser, step S4 is pulsed laser S3 applies continuous high-speed laser during the first layer of high-speed laser cladding; the laser form is a shaped circular flat top light with a spot diameter of 3mm, the continuous laser beam power is 600W, the scanning speed is 3000mm / min, the powder feed rate is 0.4r / min, and the overlap rate is 70%; S4. Apply pulsed laser during high-speed laser cladding of the second to fourth layers. The pulse laser frequency is 400 Hz, the pulse width is 100 μs, and the power is 400 W. Comparative Example 6 Based on Example 1, the difference lies in steps S3-S4, which are both continuous high-speed lasers. S3. Continuous high-speed laser during the first layer of high-speed laser cladding; the laser morphology is rectangular Gaussian light, the laser morphology is a shaped circular flat-top light, the circular flat-top light spot diameter is 3mm, the continuous laser beam power is 600W, the scanning speed is 3000mm / min, the powder feed rate is 0.4r / min, and the overlap rate is 70%; S4. Apply continuous high-speed laser during high-speed laser cladding of the second to fourth layers; the laser morphology is rectangular Gaussian light, the laser morphology is a shaped circular flat-top light, the spot diameter of the circular flat-top light is 3mm, the continuous laser beam power is 600W, the scanning speed is 3000mm / min, the powder feed rate is 0.4r / min, and the overlap rate is 70%.

[0035] Comparative Example 7 Based on Example 1, the difference lies in steps S3-S4, which are both pulsed lasers. S3. Apply pulsed laser during high-speed laser cladding of the first layer, with a pulse laser frequency of 400 Hz, a pulse width of 100 μs, and a power of 400 W; S4. Apply pulsed laser during high-speed laser cladding of the second to fourth layers. The pulse laser frequency is 400 Hz, the pulse width is 100 μs, and the power is 400 W.

[0036] Comparative Example 8 Based on Example 1, step S1 does not add MoAlB powder. Instead, the nickel-based alloy powder is mixed in a roller mixer at a speed of 30 rpm for 12 hours and then dried in an electric constant temperature vacuum drying oven at 110°C for 60 minutes. The nickel-based composite coating powder includes the following components by mass fraction: 25wt% Cr, 7wt% Fe, 4.5wt% Si, 7wt% B, 0.5wt% C, 0.005wt% O, with the balance being Ni, and the powder particle size is 40-100μm. The other steps are consistent with Example 1. This will result in the laser cladding layer primarily comprising the nickel-based alloy body, excluding the large amount of hard phase generated in situ by the chemical reaction. Therefore, it is difficult to effectively strengthen the material surface, and its wear resistance is poor.

[0037] Table 1

[0038] By comparing Example 1 with Examples 4, 5 and Comparative Example 1, a circular flat-top spot was used for laser cladding of the 2nd to 4th layers. The circular flat-top spot has the advantage of uniform energy distribution and is suitable for high-efficiency large-area laser cladding. However, as the spot diameter increases, the spot energy gradually decays, resulting in insufficient energy input to the molten pool, a reduced dilution rate, reduced bonding strength with the substrate, and the cladding layer is prone to cracks. Experiments have shown that when the spot diameter is 3-4mm, a cladding layer with good forming quality and no cracks can be obtained. When the spot diameter is greater than 5mm, the forming quality of the cladding layer is low, and the tendency to crack significantly increases. In addition, it was unexpectedly found that the magnetic properties of Example 1, such as coercive force, are significantly lower than the coercive force levels of Examples 4, 5 and Comparative Example 1, showing good demagnetization and good repulsion properties for magnetic abrasive particles.

[0039] Comparing Example 1 with Comparative Example 2, when Comparative Example 2 used a circular Gaussian spot, widely used in the engineering community, for laser cladding of nickel-based alloy powder, the uneven distribution of laser energy resulted in high-energy materials at high temperatures at the center of the circular spot, while low-energy materials at the edges were at lower temperatures. This resulted in significant thermal stress and a high risk of crack formation. Comparing Example 1 with Comparative Example 3, Comparative Example 3 used a highly wear-resistant iron-based alloy powder system, widely used in the engineering community, for laser cladding. While this also improved coating hardness and strengthened the material surface, the internal hard phase distribution of the coating was difficult to control, and the coating material was highly magnetic. This could easily lead to magnetic particles being absorbed and rotated into turbine components during application, resulting in significant safety hazards that should not be ignored.

[0040] Comparing Example 1 with Examples 6 and 7 and Comparative Example 4 reveals that varying the laser pulse frequency and pulse width affects the quality of the cladding layer. Increasing the pulse frequency increases the accumulated thermal stress in the molten pool, making cracks more likely to form during cooling. Increasing the pulse width prolongs the laser action time, increasing the heat input to the molten pool, leading to increased penetration and a more complex stress distribution within the cladding layer. Therefore, selecting the appropriate laser pulse frequency and pulse width is crucial for achieving a high-quality, crack-free cladding layer.

[0041] By comparing Example 1, Comparative Examples 5, 6, and 7, the structural design of the cladding layer has a certain impact on the forming and mechanical properties of the cladding layer. Pulse laser cladding technology has a laser shock strengthening effect on the cladding layer while performing laser cladding. Therefore, as the number of pulse laser cladding layers increases, the hardness of the cladding layer is greatly improved. However, it is precisely because of the existence of the pulse laser shock strengthening effect that cracks are easily generated on the surface of the cladding layer. The rectangular Gaussian spot used in Comparative Example 4 has the characteristics of high central energy, Gaussian distribution of surrounding energy, and rapid decay toward the surrounding area. Its energy distribution is uneven, so the cladding layer is prone to solidification defects.

[0042] The above embodiments are merely preferred technical solutions of the present invention and should not be construed as limiting the present invention. The embodiments and features in the embodiments of this application may be arbitrarily combined with each other unless they conflict. The scope of protection of the present invention shall be the technical solutions described in the claims, including equivalent alternatives to the technical features of the technical solutions described in the claims. Equivalent alternatives and improvements within this scope are also within the scope of protection of the present invention.

Claims

1. A method for preparing a structured nickel-based wear-resistant composite coating by high-speed laser cladding, characterized in that: The method comprises the following steps: S1: Mix the nickel-based composite coating powder with a roller mixer and then bake the powder; S2 adds the dried powder into the powder barrel; S3 uses coaxial powder feeding to perform high-speed laser cladding. When high-speed laser cladding the first layer, pulsed laser is applied to form a serrated layer in the subsurface area of ​​the substrate; when high-speed laser cladding the second to fourth layers, continuous high-speed laser is applied to form a flat layer; and so on, after each cladding of a serrated layer, three flat layers are clad, wherein the thickness of the first layer is 200-250μm, and the thickness of the second to fourth layers is 400-500μm; a structured nickel-based wear-resistant composite coating prepared by high-speed laser cladding is obtained.

2. The method according to claim 1, wherein: The nickel-based composite coating powder in step S1 includes the following components by mass fraction: Cr17-27wt%, Fe6-8wt%, Si4-5wt%, B5-8wt%, C0.3-0.7wt%, O less than 0.02wt%, and the balance is Ni, and the powder particle size is 40-100 μm.

3. The method according to claim 1, wherein: In step S1, reinforcement powder, specifically MoAlB compound powder, is further added to the nickel-based composite coating powder.

4. The method according to claim 3, characterized in that The amount of reinforcement powder added accounts for 25-35 wt% of the total amount of nickel-based composite coating powder, preferably 30 wt%.

5. The method according to claim 3, characterized in that The MoAlB compound powder has a purity of more than 95%, a particle size of 20-40 μm, and an equivalent particle size deviation rate within 10%.

6. The method according to claim 1, wherein: In step S1, the mixing time is 11-14 hours, the speed is 20-40 rpm, and then the powder is placed in an electric constant temperature vacuum drying oven at 100-120° C. and dried for 40-120 minutes.

7. The method according to claim 1, characterized in that The scanning speed adopted in step S3 is 3000-4000 mm / min, the dilution rate of the cladding layer is low, the powder feeding rate is 0.4-1.0 r / min, and the overlap rate is 50-70%, thereby improving the cladding efficiency.

8. The method according to claim 1, characterized in that The pulse frequency of the pulsed laser cladding technology in step S3 is 100-1000 Hz, the pulse width is 50-600 μs, and the power is 400-600 W; the continuous laser beam power is 600-1100 W, so that the cladding layer has a specific temperature gradient transient non-equilibrium solidification feature.

9. The method according to claim 1, characterized in that The beam shaping technology in step S3 refers to the laser shape being a shaped circular flat top light or rectangular Gaussian light, the spot diameter of the circular flat top light is 3-7 mm, and the spot size of the rectangular Gaussian light is 4 mm×4 mm.

10. The method according to claim 1, characterized in that In step S3, the side of the hard layer of the cross section of the sawtooth layer forms an angle of 80-90° with the horizontal plane; the cross section of the sawtooth layer has a size of 3-5 mm×3-5 mm, and a spacing of 5 mm.